A case of ectopic pregnancy in scar of previous cesarean - Loayza, Juan Carlos (2019)
Ectopic pregnancy in the scar of a previous cesarean section refers to the implantation of the external blastocyst of the endometrium at the site where the previous hysterotomy was performed. We report the case of a 32-year-old patient who was admitted to the emergency service of the Vitarte Hospital in Lima-Peru, with 7,5 weeks of gestation due to the last menstruation and ultrasound scan, previously performed 7 years ago. Exploratory laparotomy was performed with an incision on the uterine isthmus on a scar of previous cesarean section, taking out the gestational sac and performing curettage on the implantation site. The case is described by its rarity and potentially catastrophic consequences that endanger the life of the mother.